Analisa Performansi Protokol 802.11P Pada Routing AODV di Jaringan VANET (Vehicular Ad-hoc Network) - Ahmad Ridwan (Teknik Informatika, Politeknik Negeri Tanah Laut, 2022)
Intelligent Transportation Systems have experienced remarkable developments in the past decade, and advances in communication technology have a significant role in the success of intelligent transportation systems. Communication systems between vehicles are essential requirements for intelligent transportation systems. Vehicular Ad-hoc Network (VANET) technology is suitable for communication between vehicles. In its implementation, VANET faces several challenges such as disconnection, coverage area, dynamic topology changes, connectivity, signal strength, delay time, and throughput. One of the problems faced by VANET is routing. Routing on VANET is challenging due to high mobility, network topology disruption, and path selection. In this paper, simulation is conducted to obtain AODV routing performance on VANET networks based on the quality of service with scenarios 20 and 30 nodes. AODV routing was chosen because it has the best performance in its class. From the simulation results obtained an end to end delay 20 nodes 21,1247 and 30 nodes 22,0781, with an increase of period to end 4.5% occurs at 30 nodes compared to 20 nodes, packet drop obtained for 20 nodes 0.8284, and 30 nodes 0.7888 with a PDRR reduction ratio of 4.7% from 20 nodes. Furthermore, the throughput values obtained in the simulation are 20 nodes 272.59 and 30 nodes 347.92, with a rate of 20 and 30 nodes of 27%. Package delivery ratio for 20 nodes 2980, and 30 nodes 4868, with a standard of comparison of successful packages sent 38%. Keywords: AODV, VANET, Intelligent Transportation System, Routing